Living Qur’an Dalam Ruwatan Pernikahan Bagi Anak Sendhang Kapit Pancuran di Desa Sidang Bandar Anom Kecamatan Rawajitu Utara Mesuji Lampung - Heni Astuti; Ikhwanuddin; Muhammad Nur Amin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study discusses the concept of living qur’an in the tradition of wedding ruwatan for children of sendhang kapit pancuran in Sidang Bandar Anom village, North Rawajitu District, Mesuji Regency, Lampung Province using Edmund Husserl’s Phenomenology approach. The researcher found that the tradition of wedding ruwatan for children of sendhang kapit pancuran in Sidang Bandar Anom village is a form of practicing the values of the qur’an (living qur’an) that are internalized in local culture. Through Husserl’s phenomenology approach, it is revealed that community interprets this ritual as a means of prayer, spiritual protection, and requests for safety and clessings in marriage. The most impertant finding is that the teachings of the qur’an are not only practiced normatively, but also brought to life in a contextual and meaningful cultural dimension for the local cummunity.